2005
DOI: 10.1111/j.1540-5826.2005.00127.x
|View full text |Cite
|
Sign up to set email alerts
|

Writing in Mathematics: An Alternative Form of Communication for Academically Low-Achieving Students

Abstract: Classroom communication figures prominently in current math reform efforts. In this study, we analyze how one teacher used writing to support communication in a seventh-grade, low-track mathematics class. For one school year, we studied four lowachieving students in the class. Students wrote in journals on a weekly basis. Using classroom observations and interviews with the teacher, we developed profiles of the four students, capturing their participation in class discussions. The profiles highlighted an impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 49 publications
(64 reference statements)
5
71
0
Order By: Relevance
“…Baxter, Woodward, and Olson (2005) studied four low-achieving students and their journal entries for a year and found that journals were a valuable method for student-teacher communication. They felt that journals particularly increased the amount of communication between low-achieving students and the teacher.…”
Section: Examining Student Thinkingmentioning
confidence: 99%
See 1 more Smart Citation
“…Baxter, Woodward, and Olson (2005) studied four low-achieving students and their journal entries for a year and found that journals were a valuable method for student-teacher communication. They felt that journals particularly increased the amount of communication between low-achieving students and the teacher.…”
Section: Examining Student Thinkingmentioning
confidence: 99%
“…Some educators have used writing as a means to adjust attitudes toward and perceptions of math (Sewell, 2006;Furner & Duffy, 2002;and Mason & McFeetors, 2002). Others have assessed student thinking (Baxter, Woodward, & Olson, 2005;Burns, 2005;Gordon & Macinnis, 1993;and Countryman, 1992) or used writing as a learning mechanism for new concepts and skills (Marlow, 2006;O'Connel, Beamon, Beyea, Denvir, Dowdall, Friedland & Ward, 2005;Williams, 2003;Brandenburg, 2002;Cooley, 2002;Koirala, 2002, Burns & Silbey, 2001McIntosh & Draper, 2001;Baker, 1999;and Fuqua, 1997).…”
mentioning
confidence: 99%
“…It is addressed as an important competence in learning school mathematics in research (see f. e. Kilpatrick, 2001;Lithner, 2008;Niss, 2003) and in several countries' curricula (National council of teachers of mathematics, 2003;Skolverket, 2011). Reasoning in school mathematics is considered an essential practice, both to facilitate students' meaning making in mathematics and to make the learning visible for students as well as for teachers (Baxter, Woodward & Olson, 2005). Earlier studies (Bieda, Drwencke & Picard;Sidenvall, 2015;Stylianides, 2009) have pointed out that the opportunities for students' reasoning can be very limited when relying on the mathematics textbook.…”
Section: Reasoning Competence In Mathematicsmentioning
confidence: 99%
“…However, reasoning in mathematics education is also stressed as an important competence in school mathematics by several researchers (Hanna, 2000;Kilpatrick, 2001;Lithner, 2008;Niss & Højgard Jensen, 2002). For example, in direct relation to the mathematics curriculum and the school classroom, Baxter et al (2005) and Cobb (2002) highlight that students' reasoning can potentially contribute to visualizing important aspects of how students have interpreted the specific mathematical content being processed. Further, it is stressed that by letting students argue and explain their thinking, the comprehension of mathematical content is being supported (Boaler & Staples, 2008).…”
Section: Reasoning In Mathematics Educationmentioning
confidence: 99%
See 1 more Smart Citation